Photoactivity of MWCNTs modified α-Fe2O3 photoelectrode towards efficient solar water splitting. (November 2015) - Rai, Snigdha; Ikram, Ashi; Sahai, Sonal; Dass, Sahab; Shrivastav, Rohit; Satsangi, Vibha R.
Abstract: MWCNTs (Multiwalled Carbon Nanotubes) modified α-Fe2 O3 (hematite) photoelectrodes have been investigated for their possible application in hydrogen generation via photoelectrochemical (PEC) splitting of water. Enhanced photoresponse seen in comparison to the pristine α-Fe2 O3 films is credited to the effective charge facilitation and charge separation provided by MWCNT conducting support. 0.2 wt% MWCNTs modified α-Fe2 O3 thin film exhibited the maximum photocurrent density of 2.8 mA/cm 2 at 0.75 V/SCE. Measured values of flat band potential, donor density, resistance, Applied bias photon-to-current efficiency (ABPE) and Incident-photon-to current-conversion efficiency (IPCE) support the observed enhancement in photocurrent. Graphical abstract: Highlights: Fe2 O3 -MWCNT has been found to be beneficial in photoelectrochemical water splitting. Ballistic pathway provided by MWCNTs is the main cause of improved photoactivity. Fe2 O3 -MWCNT composite is found to be superior than previously reported bilayered systems. Agglomeration issue in MWCNTs has been resolved by optimizing the concentration.